Effects of psilocybin therapy on personality structure - Erritzoe,D; Roseman,L; Nour,MM; MacLean,K; Kaelen,M; Nutt,DJ; Carhart-Harris,RL (Acta Psychiatrica Scandinavica, 2018)
ObjectiveTo explore whether psilocybin with psychological support modulates personality parameters in patients suffering from treatmentresistant depression (TRD).MethodTwenty patients with moderate or severe, unipolar, TRD received oral psilocybin (10 and 25 mg, one week apart) in a supportive setting. Personality was assessed at baseline and at 3month followup using the Revised NEO Personality Inventory (NEOPIR), the subjective psilocybin experience with Altered State of Consciousness (ASC) scale, and depressive symptoms with QIDSSR16.ResultsNeuroticism scores significantly decreased while Extraversion increased following psilocybin therapy. These changes were in the direction of the normative NEOPIR data and were both predicted, in an exploratory analysis, by the degree of insightfulness experienced during the psilocybin session. Openness scores also significantly increased following psilocybin, whereas Conscientiousness showed trendlevel increases, and Agreeableness did not change.ConclusionOur observation of changes in personality measures after psilocybin therapy was mostly consistent with reports of personality change in relation to conventional antidepressant treatment, although the pronounced increases in Extraversion and Openness might constitute an effect more specific to psychedelic therapy. This needs further exploration in future controlled studies, as do the brain mechanisms of postpsychedelic personality change.